Islamic Social Reporting (ISR) Analysis in Indonesia and Malaysia - Nofitasari, Wiwit Ayu; Endraswati, Hikmah (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2019)
The purposes of this study are to examine the effect of company size, profitability, the board of commissioners, proportion of independent commissioners, and frequency of meetings on the level of Islamic Social Reporting (ISR) in Indonesia and Malaysia and to test whether there are difference ISR systems in Indonesia and Malaysia. The sample of this study is ten companies that issued Sukuk at Indonesia Sharia Stocks Index and eight companies on Malaysia Stock Exchange in 2013 2017. Multiple regression and different tests are used in this research as analysis techniques. The results show that the size of the company affects the level of ISR positively in Indonesia, but not in Malaysia. Profitability, board size, and the proportion of independent commissioners do not affect ISR levels in both countries. T he frequency of board of commissioner meetings affect ISR levels in Indonesia and Malaysia positively, and there is difference ISR system in the two countries. This research implies that there is a need for regulations considering ISR disclosure in Indonesia to improve the quality of ISR disclosure to the stakeholders.Abstrak:Tujuan penelitian ini adalah untuk menguji pengaruh ukuran perusahaan, profitabilitas, dewan komisaris, proporsi komisaris independen, dan frekuensi rapat terhadap tingkat ISR (Islamic Social Reporting) di Indonesia dan Malaysia, dan untuk menguji apakah ada perbedaan ISR di Indonesia dan Malaysia. Sampel penelitian ini adalah 10 perusahaan yang menerbitkan Sukuk di Indeks Saham Syariah Indonesia dan 8 perusahaan di Bursa Saham Malaysia pada tahun 2013-2017. Dalam analisis, penelitian ini menggunakan teknik regresi berganda (regresi berganda) dan uji beda (uji beda). Hasil penelitian menunjukkan bahwa ukuran atau besarnya perusahaan berpengaruh positif secara signifikan terhadap tingkat ISR di Indonesia namun tidak terbukti di Malaysia. Sementara itu, profitabilitas, ukuran dewan komisaris, dan proporsi dewan komisaris independen tidak berpengaruh terhadap tingkat ISR di Indonesia dan Malaysia. Frekuensi rapat dewan komisaris berpengaruh positif secara signifikan terhadap tingkat ISR di Indonesia dan Malaysia; dan ada perbedaan tingkat ISR di Indonesia dan Malaysia. Implikasi dari penelitian ini adalah perlunya adanya regulasi tentang pengaturan ISR di Indonesia untuk meningkatkan kualitas penyajian ISR kepada pemangku kepentingan.